Gestão do patrimônio cultural em Minas Gerais: novas dimensões e paradoxos - Flávia de Assis Lage (2014)
This research aims at understanding the participation of different social actors in the management of cultural heritage protection at the federal, state and municipal levels. The policy of cultural heritage of the state of Minas Gerais ICMS Patrimônio Cultural was taken as reference for that review. This policy was a pioneer action in the country. This policy is constituted as an induction to the municipalization of protection of cultural heritage initiative, resulting in decentralization, according with the guidelines of the Brazilian Constitution of 1988. On this study, one of the research methods focused was the method of interviews with social actors, just to try to understand the involvement of them in conservation management cultural heritage. The results of this research point to the importance of integration between the various institutional levels - federal, state and municipal - the protection of cultural heritage and the importance of effective participation of civil society.